Optimization of Coagulant Dosage for Suko River Water Treatment - syarifah aini; H.D. Wahyudi; Kukuh Priyono (Eksergi, 2021)
Sungai Suko, Drono village, Ngawen sub-district, Klaten district, is located near residential area and tofu factory, the possibility of water contamination is quite high, which is caused by household waste. This river water can be processed into clean water by a coagulation process of the Jar Test method using coagulant alum, PAC and chlorine. The purpose of this study was to determine the optimum dose of coagulant in processing Suko river water into clean water using the Jar test method and knowing which coagulant is most suitable for processing the Suko river water into clean water. This research method is to use the Jar Test experiment to determine the optimum coagulant dose in processing Suko river water into clean water. The quality of the water samples before the experiment were tested which included the physical parameters, i.e. temperature, color, odor, and turbidity, also the chemical parameters, i.e. Fe, hardness, CO2, alkalinity, pH, COD, BOD, then the experimental results will determine the level of water clarity. The results showed that the optimum alum content in the experiment was 120 ppm by adding 6 mL of alum to 500 mL of water, the optimum level of PAC in the experiment is 200 ppm by adding 10 mL of PAC to 500 mL of water, and the optimum chlorine level in the experiment is 160 ppm by adding 8 mL of chlorine to 500 mL of water.